HOW MUCH OF THE LOCAL KNOWLEDGE ABOUT MEDICINAL PLANTS IS INCLUDED IN PUBLIC HEALTH POLICIES? A CASE STUDY FROM SOUTH BRAZIL - Giraldi, Mariana (2016)
The incorporation of traditional medicine in public health policies has been proposed by the World Health Organization (WHO). In Brazil this is reflected in RENISUS, an official list of medicinal plants of interest to the public health care system, with medicinal potential. Despite being an advance, this list reveals only a fraction of the biological and cultural diversity of Brazil. Using ethnobotanical data from two rural communities in Southern Brazil (Sertão do Ribeirão and Costa da Lagoa, Florianópolis municipality) we compared the RENISUS list with the lists of medicinal plants traditionally used. The similarity between the ethnobotanical lists was 26.32%, and between RENISUS and each ethnobotanical list was less than 5%. These results indicate the need to broaden the approach of the public health policies. The systematization of ethnobotanical data can be an interesting strategy for it.